The Philosophy of Law in Enforcing Criminal Liability for Nominee Accounts: A Comparative Study of Indonesia and Pakistan - Ginting, Beren Rukur; Suarda, I Gede Widhiana; Rato, Dominikus; Anggono, Bayu Dwi; Abbas, Shahzada Rahim (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: The use of nominee accounts is an increasingly prevalent phenomenon in the practice of financial crimes, such as money laundering, tax evasion, and the financing of other criminal acts. The nominee account is basically used to disguise the identity of the actual beneficial owner, thus posing a serious challenge in the enforcement of criminal responsibility.Purposes of the Research: This study aims to analyze the concepts and foundations of legal philosophy, especially justice, legal certainty, and usefulness in the enforcement of criminal liability for the use of nominee accounts in Indonesia and Pakistan, as well as compare the positive legal arrangements that apply in the two countries.Methods of the Research: This research uses normative legal research methods with approaches to legal philosophy, legislation, and comparative law.Results Main Findings of the Research: The findings of the study show that philosophically, the enforcement of criminal liability against nominee accounts in Indonesia and Pakistan is based on efforts to realize substantive justice by penetrating the formalities of legal ownership to reveal the true beneficial owners. From the perspective of legal certainty, both Indonesia and Pakistan still face challenges due to the lack of an explicit and comprehensive regulation of nominee accounts, so law enforcement often relies on the interpretation of other criminal norms, such as money laundering and banking crimes. Meanwhile, from the aspect of utility, regulation and law enforcement of nominee accounts are directed to maintain financial system stability, prevent abuse of the banking system, and protect the interests of the community and the state. Legally positive, Indonesia regulates criminal liability related to nominee accounts indirectly through the Money Laundering Act, banking regulations, and policies related to beneficial ownership, while Pakistan regulates it through an anti-money laundering legal framework and financial sector regulations that emphasize ownership transparency and due diligence obligations. This comparison shows that although the two countries have similar normative approaches, the difference lies in the explicit level of regulation and effectiveness of their implementation. Therefore, it is necessary to strengthen the philosophical foundation and harmonize legal arrangements to ensure the enforcement of fair, definite, and beneficial criminal liability for the practice of using nominee accounts.